Pengaruh Pembelajaran Bahasa Indonesia Terhadap Pengembangan Kesantunan Berbahasa Siswa Kelas XI SMA Kristen YPKPM Ambon - Hahury, Jessy Juniu (P3M POLITEKNIK NEGERI AMBON, 2024)
The aims of this research are: 1). To explain the influence of Indonesian language learning on students' language politeness. 2) To explain how much Indonesian language learning affects students' language politeness. The population of this study were class XI students of YPKPM Ambon Christian High School. The sample for this research was class XI students consisting of 35 students. The instruments used in this research were an Indonesian language learning questionnaire and a student language politeness questionnaire. Data analysis uses a simple linear regression test which includes a T test using the Statistical Package for the Social Science (SPSS) 18.0 for Windows. From the results of the research and discussion, it can be concluded that 1). The Indonesian language learning included in this research was proven to have a significant influence on the language politeness of class X1 students at Christian High School YPKPM Ambon 2). In this study, it was found that the variation in language politeness explained by Indonesian language learning was 67.9%, while 32.1% was explained by other variables not analyzed in the model. Keywords: Indonesian language learning, students' language polite